KOMODIFIKASI PEMBERITAAN; ANALISIS FRAMING ENTMAN PADA PEMBERITAAN PARIWISATA HALAL DI HARIAN REPUBLIKA - Ayu Dwinary D.P; Fajar Aditiya Nugraha (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
Halal tourism sector is one of prime sector for increment of national foreign exchange. The labelling of halal tourism raises argument cause by commodification of religion value that transformed into exchange value. Republika is known as a media that emphasizes Islamic issues that play a role in shaping the reality of society through the process of commodification of the news. The form of commodification that found is 124 news related on halal tourism. Commodification of the audience is carried out by prioritizing NTB and other Regions as the main destinations. The framing analysis results based on the Entman model show that Republika prioritizes sources with an interest in halal tourism as the resource person, and shows Republika's support for the theme